2019
DOI: 10.1016/j.htct.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Targeted therapy with a selective BCL-2 inhibitor in older patients with acute myeloid leukemia

Abstract: Background Older patients with acute myeloid leukemia are particularly difficult to treat, as they have a high risk of comorbidities, poor performance status and less tolerability to chemotherapy, as well as a more aggressive disease biology, responsible for the resistance to treatment. There is a need to explore novel therapeutic agents that are more effective and tolerable. Venetoclax, a BCL-2 inhibitor is a promising agent, as BCL-2 overexpression is present in 84% of acute myeloid leukemia pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Reductions in Bcl-2 expression have been shown to promote primary and acquired resistance to venetoclax by alternate pathway activation and upregulated expression of other anti-apoptotic proteins such as MCL-1 and Bcl-xL[ 53 ]. A study of AML cell lines in vitro showed a definite and inverse correlation with the ratios of Bcl-2/MCL-1 transcripts and venetoclax sensitivity suggesting the importance of MCL-1 effect on sensitivity[ 54 ]. Similarly, Niu et al[ 55 ] demonstrated that Bcl-2/MCL-1 transcript ratio may represent a potential biomarker in predicting response[ 55 ].…”
Section: Mechanisms Of Venetoclax Resistancementioning
confidence: 99%
“…Reductions in Bcl-2 expression have been shown to promote primary and acquired resistance to venetoclax by alternate pathway activation and upregulated expression of other anti-apoptotic proteins such as MCL-1 and Bcl-xL[ 53 ]. A study of AML cell lines in vitro showed a definite and inverse correlation with the ratios of Bcl-2/MCL-1 transcripts and venetoclax sensitivity suggesting the importance of MCL-1 effect on sensitivity[ 54 ]. Similarly, Niu et al[ 55 ] demonstrated that Bcl-2/MCL-1 transcript ratio may represent a potential biomarker in predicting response[ 55 ].…”
Section: Mechanisms Of Venetoclax Resistancementioning
confidence: 99%
“…Many agents can reduce MCL1 expression in vitro including chemotherapy and HMA. 28 Venetoclax in combination with HMA in newly diagnosed elderly AML patients demonstrated 67% CR and median OS of 17.5 months. 29 The responses occurred in patients with poor risk mutations; TP53 and FLT3 mutations, similar to those with IDH and NPM1 mutations.…”
Section: B-cell Leukemia/lymphoma-2 (Bcl2) Inhibitormentioning
confidence: 90%
“…Another important, but less understood, aspect of cancer cells sensitivity to venetoclax is their genetic backgrounds. Cancer cells baring some types of genetic aberrations such as chromosomal rearrangement [ 71 ], IDH1/2, or WT1 point mutations [ 70 , 91 ] are exquisitely sensitive to venetoclax. The molecular basis of this sensitivity has been linked to high level of BCL-2 in these cells; however, additional factors might be determinant in this phenomenon.…”
Section: Resistance Of Cancer Cells To Venetoclaxmentioning
confidence: 99%